Audiovisual techniques in translator education: Pedagogical applications and learning outcomes - Bakirova Khilolakhon Botiraliyevna (Universal Teaching and Learning Journal, 2025)
Purpose: This article examines the pedagogical role of audiovisual techniques in translator education and explains how audiovisual materials contribute to the development of linguistic, cultural, and professional competencies in translation students. Research Methodology: The study employs a qualitative descriptive design through a systematic review and synthesis of scholarly literature and documented teaching practices in translation studies, applied linguistics, and language pedagogy. The analysis focuses on commonly used audiovisual techniques in training—such as subtitling, dubbing, voice-over, film clips, recorded interviews, and multimedia presentations and evaluates their instructional objectives, implementation strategies, and learning outcomes in translator training. Results: The findings indicate that audiovisual techniques enhance students’ listening comprehension and spoken-language awareness, strengthen contextual and cultural interpretation through multimodal cues (e.g., gestures, setting, and non-verbal communication), and improve professional readiness by simulating industry constraints (time, space, synchronization, and audience reception). Audiovisual tasks also increase student motivation, engagement, and learner autonomy by making learning more interactive and market-relevant. Conclusions: Integrating audiovisual techniques into translation curricula supports practice-oriented learning and better aligns translator training with contemporary professional demands, provided that materials and tasks are carefully selected and scaffolded by instructors. Limitations: This study is literature-based and does not include classroom experiments or longitudinal measurement of learning gains. Contribution: Future research should conduct empirical and longitudinal classroom studies to quantify competence development and explore the integration of emerging digital technologies in audiovisual translator training.